Using biodiversity features to promote an Ecosystem-Based Conservation framework in terrestrial ecosystems - Florence Godfrey Tarimo; Francis Moyo; Linus Kasian Munishi (PLoS ONE, 2025)
Biodiversity features are important indicators for monitoring conservation success and have been adopted to assess the extent of biodiversity loss in ecosystems affected by anthropogenic pressures. Protected areas (PAs) form the basis of the modern conservation framework and are the heart of conserving biodiversity. Despite PAs being the cornerstones for biodiversity conservation, they are limited in extent and their ability to inclusively conserve and safeguard biodiversity. We performed a literature review and spatial analysis across terrestrial ecosystems in Tanzania to investigate how biodiversity features can guide and promote an ecosystem-based conservation approach. We compiled biodiversity features for three taxonomic groups (plants, vertebrates, and invertebrates), resulting in a total sum of 22,987 features across eight terrestrial ecosystems in Tanzania. Our results revealed that the montane forest ecosystem had more total reported biodiversity features than other ecosystems, with <1/3 of its area protected. For other ecosystems, our three biodiversity features varied widely with the level of protection. PAs encompassed approximately 41%, while the remaining lacked formal protection measures. Invertebrates are often not considered when designing PA systems or building conservation approaches, highlighting the need to extend conservation efforts beyond the current framework. An ecosystem-based conservation framework is needed to extend conservation efforts outside PAs to address substantial taxonomic and spatial gaps in conservation actions to achieve biodiversity conservation targets under the Post-2020 Global Biodiversity Framework .